CLOSED-LOOP CONTROL OF OXYGEN-CONVERTER MELTING - V. S. Bogushevsky; S. V. Zhuk; S. G. Melnik; E. N. Zubova (Литьë и металлургия, 2013)
The mathematical model of Fe – C-melt decarbonization, with the assistance of the theory of critical concentrations was developed in this work. The model takes into account the kinetics of the process of removing carbon from the melt in the foreign – and intradiffusion limiting process of decarburization. The algorithm of the model is implemented in an automated process control system of converter smelting. Pilot plant testing of a mathematical model of decarburization process control BOF melt showed a significant improvement of technical and economic parameters of steelmaking.